Educação em economia popular solidária: experiências pedagógicas que libertam? - Pielke, Luciane Rocha Ferreira (Universidade do Vale do Rio dos Sinos, 2018)
The present thesis has as its theme the educational phenomenon that happens in the universe of the Social Movement of the Popular Solidarity Economy. The research took place in two educational experiences, born of public policy projects, governed financed by SENAES: the second version of the Centro de Formação e Assessoria Técnica em Economia Solidária (CFES Regional Sul/ 2013-2017) and the Municipal Project of Integrated Actions of Solidarity Economy of São Leopoldo/RS (2013/2016). The main objective of this study is to investigate the meanings - individual and collective - attributed by the people who participated in the educational processes, as well as perceive in them possibilities and limits for the construction/consolidation of a public policy of education and technical advice in Solidary Economy. Between the lines of this comprehensive (re)reading, it was intended to identify how the pedagogical process happened through the practices of participation and dialogue, verifying how the life experiences contribute to a possible awareness and liberation of the people involved. The theoretical reference was based on the Phenomenological view from Merleau-Ponty, in line with Popular Education in Paulo Freire and with the Systematization of Experiences according to Oscar Jara and Danilo Streck e Telmo Adams. The theoretical dimensions of the (de)colonial epistemologies according to Frantz Fanon, Catherine Walsh, Walter Mignolo, Danilo Streck and Telmo Adams, Fernanda F. Bragato and feminists collaborate to broaden the reflections in the research. Among the results, we highlight: the potential of sorority as pedagogical mediation among women; the epistemologies of the daily feminine as existential basis of the production of senses, meanings and knowledge liberating oneself; the (re)signification of concepts and practices that are fundamental to the experience of education in Solidary Economy as a policy strengthening strategy; the challenge of living solidarity education as an educational principle of training/education in Solidary Popular Economy; the re-signification of the meanings and practices of participation and dialogue as pedagogical instruments of self-management possible.
Keywords: Educação/formação; Economia popular solidária; (Des)colonialidade; Educação popular; Fenomenologia existencial; Education/training; Popular solidarity economy; (De)coloniality; Popular education; Existential phenomenology; ACCNPQ::Ciências Humanas::Educação